Effect Of Copper On The Non-Specific Immune Response Of Puntius Gonionotus Challenged With Aeromonas Hydrophila - Jayawardena, P.A.H.L. (1996)

(untitled)
This study is focused on toxicity of copper and its effects on the immune response of P. gonionotus. The median lethal concentration of copper (LC50) on P. gonionotus (56.9±4.5 g) at 12, 24, 48, 72 and 120 hours was estimated as 2.17, 0.91, 0.57, 0. 53, 0.42 mg/L respectively. Fish were intraperitonealy injected with three different doses (4.5 x 105, 4.5 X 107 and 4.5 x 109 CFU/mL) of formalin killed A. hydrophila (0.1 mL) and the immune responses were monitored using haematological and serological assays over a period of 30 days post-injection. The assays used were total WBC counts, lysozyme, NBT, total protein, total immunoglobulin and haematocrit levels. The immune responses with the highest magnitude were observed among fish injected with 4.5 x 109 and the lowest among 4.5 x 105 CFU/mL. The responses were observed to be both time and dose dependent.To find the effect of copper on the immune response, fish were exposed to different sublethal concentrations of copper, determined at 10%, 20%, and 30% of 96 hour LC50 for 71 days. After 56 days of initial exposure, fish were challenged with 0.1 mL of 4.5 x 105 CFU/mL formalin killed A. hydrophila. The immune responses were monitored using the same immunological assays mentioned above withdrawing non-lethal blood samples at 14, 28, 56, 61, 66 and 71 days of exposure to copper. Though a depletion of protein and immunoglobulin titres in plasma were observed at the initial exposure to copper, it did not influence the increased titres demonstrated against the bacterial challenge in any of the treatments. In contrast, the WBC counts increased during the initial exposure to copper. WBC counts, lysozyme and NBT assays showed suppressed immune responses after challenging with bacteria compared to the control group. But the responses observed at the lowest concentration (0.05 mg/L) of exposure to copper, were similar to that of the control in most of the cases. This suggests the absence of immunosuppressive effects at 0.05 mg/L of copper.